2008
DOI: 10.1111/j.1478-3231.2007.01646.x
|View full text |Cite
|
Sign up to set email alerts
|

An enormous hepatitis B virus‐related liver disease burden projected in Vietnam by 2025

Abstract: Over the next two decades, universal infant HBV vaccination will reduce chronic HBV prevalence in Vietnam but HBV-related liver disease burden will continue to rise. A national HBV strategy is required to address this expanding burden of liver disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
66
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 64 publications
(68 citation statements)
references
References 40 publications
0
66
0
2
Order By: Relevance
“…However, the HBV-related liver disease burden from cirrhosis and HCC will continue to rise on the basis of the estimated incidence with HBV DNA levels from the Taiwanese Risk Evaluation of Viral Load Elevation and Associated Liver Disease/Cancer in HBV (REVEAL-HBV) study [47,48]. Estimated HBV-related mortality is expected to increase from 12,600 in 1990 to 40,000 in 2025 [49]. A national HBV strategy is required to address this expanding burden of liver disease.…”
Section: Prevention Of Mother-to-child Transmissionmentioning
confidence: 99%
“…However, the HBV-related liver disease burden from cirrhosis and HCC will continue to rise on the basis of the estimated incidence with HBV DNA levels from the Taiwanese Risk Evaluation of Viral Load Elevation and Associated Liver Disease/Cancer in HBV (REVEAL-HBV) study [47,48]. Estimated HBV-related mortality is expected to increase from 12,600 in 1990 to 40,000 in 2025 [49]. A national HBV strategy is required to address this expanding burden of liver disease.…”
Section: Prevention Of Mother-to-child Transmissionmentioning
confidence: 99%
“…17 Mathematical models estimate nationally that by 2013, the number of people with chronic HBV infection will reach its peak at 8.6 million cases and then decrease to 8 million by 2025, as a direct impact of the universal infant vaccination. 42 However, the prevention of new infections does not affect the progression of the already infected individuals, and thus the estimates suggest liver cancer and liver cirrhosis cases will continue to increase: liver cirrhosis will increase from 36 500 cases in 2005 to 58 600 in 2025 and liver cancer will increase from 15 600 in 2005 to 25 000 in 2025. 42 As a result, the estimated annual HBV-related deaths will increase from 23 300 in 2005 to 40 000 in 2025.…”
Section: Burden Of Viral Hepatitis and Liver Diseasesmentioning
confidence: 99%
“…42 However, the prevention of new infections does not affect the progression of the already infected individuals, and thus the estimates suggest liver cancer and liver cirrhosis cases will continue to increase: liver cirrhosis will increase from 36 500 cases in 2005 to 58 600 in 2025 and liver cancer will increase from 15 600 in 2005 to 25 000 in 2025. 42 As a result, the estimated annual HBV-related deaths will increase from 23 300 in 2005 to 40 000 in 2025. 42 Ngo et al have found that liver cancer and liver diseases were the fourth and sixth causes of deaths among males, respectively, and that liver cancer was the third cause of death among females, between 15 and 59 years of age.…”
Section: Burden Of Viral Hepatitis and Liver Diseasesmentioning
confidence: 99%
See 2 more Smart Citations